UNIVERSAL DYNAMICS: A THEORY OF EVERYTHING WITHOUT INVENTING ANYTHING (14th CONSTRUCTAL LAW CONFERENCE | 10-11 October 2024, Bucharest, Romania, 2024)
This paper seeks to reconcile the constructal law with thermodynamics, quantum mechanics, and general relativity. Reconciling the constructal law with the more established laws of thermodynamics, we constitute a more complete and universal model of dynamics capable of explaining emergent and evolving design configurations observable throughout nature. Presented is a theory of universal dynamics, in which a core set of known universal laws can explain the universe's evolution through space, time, and all its emergent properties.
Keywords: Constructal; Quantum; Relativity; Complexity; Evolution; Emergence